Photofunctionalizable hydrogels via orthogonally clickable dendrons - Yiğit, Sezin. (Thesis (M.S.)-Bogazici University. Institute for Graduate Studies in Science and Engineering, 2011., 2011)
Hydrogels are three-dimensional, cross linked hydrophilic polymeric materials that have attracted much attention due to their key role in the development of drug delivery systems, biomolecular sensors and scaffolds for tissue engineering. Traditional synthesis of these materials has generally relied on photopolymerization of water soluble monomers. These radical based cross linking method leads to the formation of non-uniform heterogeneous gels due to the uncontrolled mechanism of the reaction. Furthermore, such hydrogels do not have a well-defined architecture and shows poor mechanical stability. Highly efficient ‘Click chemistry’ is utilized in synthesizing homogeneous and stable hydrogel networks. The set of chemical reactions that are classified as ‘click’ reactions have high yields under mild conditions, do not generate offensive by-products and have high selectivity. Photolitically functionazible PEG based hydrogels are synthesized from orthogonally functionalizable biodegradable dendrons containing alkene unit at their focal point and multiple alkyne groups at the periphery. Doubly ‘clicked’ hydrogels are first synthesized via Huisgen type [3+2] click cycloaddition and then photo patterned with thiol-ene click addition. Clicked hydrogels comprised of a polyethylene glycol based bioinert matrix that are further functionalized with dye molecules by appending thiol based ligands with positional control of the thiol-ene click chemistry. The efficiency of the Huisgen click reaction in various monomer/cross linker ratios is investigated. Photofunctionalization process is utilized by seeding the gels with florescent dye molecules. Photolithography technique is used in controlled patterning of the hydrogels under irradiation. Bioimmobilization on the hydrogel surface is demonstrated by biotin mediated attachment of FITC-Streptavidin.
Keywords: Photopolymerization.